Fluctuations of the experience of togetherness within the team over time: task-cohesion and shared understanding throughout a sporting regular season - Bourbousson, J.; Fortes-Bourbousson, M. (Ergonomics, 2017)
Based on a diagnosis action research design, the present study assessed the fluctuations of the team experience of togetherness. Reported experiences of 12 basketball team members playing in the under-18 years old national championship were studied during a four-month training and competitive period. Time series analysis (Auto-Regressive Integrated Moving Average procedures) served to describe temporal properties of the way in which the fluctuations of task-cohesion and shared understanding were step-by-step experienced over time, respectively. Correlations, running-correlations and cross-lagged correlations were used to describe the temporal links that governed the relationships between both phenomena. The results indicated that the task-cohesion dimensions differed mainly for shared understanding dynamics in that their time fluctuations were not embedded in external events, and that the variations in shared understanding tend to precede `individual attractions to the task` variations with seven team practical sessions. This study argues for further investigation of how `togetherness` is experienced alternatively as a feeling of cohesion or shared understanding.